3D–2D heterostructure of PdRu/NiZn oxyphosphides with improved durability for electrocatalytic methanol and ethanol oxidation. Issue 26 (25th June 2018) - Xu, Hui; Song, Pingping; Zhang, Yangping; Du, Yukou
Abstract : A new class of 3D–2D PdRu/NiZn oxyphosphide nanohybrids has been designed that display both enhanced catalytic activity and durability toward fuel cell oxidation reactions. Abstract : The rational design and engineering of bimetallic Pd-based nanocatalysts with both high activity and durability are of paramount significance for the practical applications of fuel cells. Herein, a new class of well-defined 2D NiZn oxyphosphide nanosheets (NiZnP NSs) have been successfully engineered to support unique 3D PdRu nanoflowers (PdRu NFs) via a facile strategy. Such nanohybrids with abundant surface active areas and modified electronic structure exhibit a great enhancement in electrocatalytic activity for the methanol oxidation reaction (MOR) and ethanol oxidation reaction (EOR), whose mass/specific activities are 1739.5 mA mg −1 /4.5 mA cm −2 and 4719.8 mA mg −1 /12.3 mA cm −2, which are 8.3/9.0 and 8.3/9.5 times higher than those of commercial Pd/C catalysts, respectively. More interestingly, with the remarkable promotional effect of NiZnP NSs, such 3D–2D PdRu/NiZn oxyphosphide nanohybrids can even retain 72.4% and 70.1% of initial catalytic activity toward MOR and EOR for 1000 potential cycles with negligible morphological or compositional variations. The successful construction of this new class of electrocatalysts opens up a new way for designing 3D–2D nanohybrids with high performance for electrochemical reactions and beyond.